Optimization Approach of the Vehicle Routing Problem with Packing Constraints Using Genetic Algorithm - Nurlita Gamayanti; Yusuf Bilfaqih; Rusdhianto EAK; M Yasya BU (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
Vehicle Routing Problem is an issue in item delivery from depot to its customers using several vehicles which have limited capacity with a purpose to minimize transportation cost. The packing constraints exist because the vehicles which are usually used in item delivery have rectangular-box shaped container. Also, the items are commonly in shape of rectangular-box. Therefore, packing or loading method is needed so that containers could load all of the items without causing damage and could ease unloading process. The purpose of this final project is to develop a model and algorithm using metaheuristics method, especially genetics algorithm in order to minimize total delivery distance. A hybrid genetics algorithm and bottom-left fill algorithm also take place to solve the packing process. This algorithm delivered average solution 0.08% worse than ant colony optimization, but had 2.93% better solution than tabu search. Keywords: Routing, Optimization, Genetics Algorithm, Packing, Bottom-Left Fill